2012
DOI: 10.1159/000342761
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies, Brain Infarcts, and Cognitive and Motor Decline in Aging (ABICMA): Design of a Community-Based, Longitudinal, Clinical-Pathological Study

Abstract: The overall goal of the Antiphospholipid Antibodies, Brain Infarcts, and Cognitive and Motor Decline in Aging study is to test the hypothesis that antiphospholipid antibodies (aPL) are associated with an increased risk of pathologically proven brain infarcts and are related to cognitive and motor decline in aging. Putative biologic mechanisms underlying the association of aPL with infarcts and the relation of aPL with clinical outcomes of cognitive and motor impairment, including vascular and other processes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The study was designed to have 80% power to detect a clinically relevant effect of aPL on infarcts, quantified by an odds ratio of 1.6 or more. 10 In the main finding presented here, we found an OR of 1.08, corresponding to an effect of aPL on infarcts, small enough to be of little clinical relevance. With such as small effect size, we do not recommend that the question be studied in a larger number of subjects.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…The study was designed to have 80% power to detect a clinically relevant effect of aPL on infarcts, quantified by an odds ratio of 1.6 or more. 10 In the main finding presented here, we found an OR of 1.08, corresponding to an effect of aPL on infarcts, small enough to be of little clinical relevance. With such as small effect size, we do not recommend that the question be studied in a larger number of subjects.…”
Section: Discussionmentioning
confidence: 42%
“…10 Briefly, aPL data were collected in the first available blood specimen (baseline), and in a subset, in the last available blood specimen (proximate to death, second time point), and in a specimen derived from a third time point in between. Repeated measures of aPL allowed for determination of persistence of aPL positivity over time and may have implications for clinical outcomes, as suggested by the literature and a consensus statement by a panel of aPL experts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation based on the meta-analysis on case-control studies was also supported by some cohort studies demonstrating the association of aCL positivity with cognitive decline and impaired motor function as follows: (1) Jacobson et al (1999) reported that the frequency of impaired neuropsychologic performance was significantly higher among young individuals with aPLs ( n = 27) as compared with controls ( p < 0.01). (2) Primary data of a longitudinal study demonstrated that aCL was positive up to 19% of subjects with impaired cognitive and motor function ( Arvanitakis et al, 2012 ); (3) Another cohort study on normal population ( n = 1895) without neurological disease including dementia indicated that aCL-positive subjects performed worst on the Mini Mental State Examination (MMSE) cognitive scale, suggesting an aCL-mediated mechanism in cognitive decline ( Homayoon et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ABICMA study (Antiphospholipid Antibodies, Brain Infarcts, and Cognitive and Motor Decline in Aging study) began in late 2009 and will test the hypothesis that aPL are associated with an increased risk of pathologically proven brain infarcts and are related to cognitive and motor decline in aging. 82…”
Section: Dementiamentioning
confidence: 99%